The spirituality of Andrei Rublev's Icon of the Holy Trinity - J. Reimer (Acta Theologica)
This article focuses on the work of Rublev who is considered to be the greatest medieval Russian Orthodox painter of icons and frescoes and whose work has influenced generations of Russian artists, theologians, writers and philosophers. It examines Rublev’s spirituality, both historically and theologically, with specific attention to the Icon of the Holy Trinity which is considered to be his most important work.